2013
DOI: 10.1002/biof.1127
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hydroxycinnamic acid sulfation by flavonoids and their conjugated metabolites

Abstract: Abstract.Hydroxycinnamic acids and flavonoids are dietary phenolic antioxidants that are abundant in our diet. Hydroxycinnamic acids are highly sulfated in vivo, and sulfotransferases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“…The nature of the substitution of (-)-epicatechin was different in the two models: whereas sulfation was favored in vivo with 73% of metabolites sulfated, methylation was the main conjugation in vitro with 77.4% of metabolites methylated. Fifteen percent of metabolites were glucuronidated in vivo, whereas such substitution could not be detected in the Caco-2 cell model, suggesting the absence of some specific uridine 59-diphospho-glucuronosyltransferase (UGT) isoforms in this model as anticipated by Vaidyanathan and Walle (2001) and Wong and Williamson (2013).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The nature of the substitution of (-)-epicatechin was different in the two models: whereas sulfation was favored in vivo with 73% of metabolites sulfated, methylation was the main conjugation in vitro with 77.4% of metabolites methylated. Fifteen percent of metabolites were glucuronidated in vivo, whereas such substitution could not be detected in the Caco-2 cell model, suggesting the absence of some specific uridine 59-diphospho-glucuronosyltransferase (UGT) isoforms in this model as anticipated by Vaidyanathan and Walle (2001) and Wong and Williamson (2013).…”
Section: Discussionmentioning
confidence: 98%
“…With the use of a multilumen perfusion catheter in humans, it was recently demonstrated that nature and substitution position of (-)-epicatechin conjugation are major determinants of the metabolic fate in the body, influencing whether the compound is effluxed into the lumen or absorbed into the blood (Actis- Goretta et al, 2013). Previous in vitro studies using Caco-2 cell monolayers as intestinal barrier model highlighted the effect of coadministration of different flavonoids on the apical and basolateral efflux of hesperetin and hydroxycinnamic acid (Brand et al, 2010;Wong and Williamson, 2013). The objective of our study was to investigate the extent of competition of (-)-epicatechin with other polyphenols to better understand its absorption and metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of sulfotransferase activity in human intestinal S9 -= - [134] a↓, the respective conjugate(s) have a lower activity than the aglycone; =, the respective conjugates have an equal activity to the aglycone; A > B, conjugate A is more active than conjugate B.…”
Section: Quercetinmentioning
confidence: 98%
“…Methylation, sulfation and glucuronidation are reported to reduce the activity of quercetin to inhibit sulfotransferases in human liver S9, while methylation does not affect the activity of quercetin to inhibit sulfotransferases in human intestinal S9. The activity of quercetin to inhibit sulfotransferases in HepG2 cells is reported to be reduced by sulfation and abolished by glucuronidation, which is likely to be due to the very low cellular uptake of the glucuronides [134].…”
Section: Inhibition Of Sulfotransferasesmentioning
confidence: 99%
See 1 more Smart Citation